Translanguaging Practices in Local Employees’ Negotiation to create Linguistic Space in a Multilingual Workplace - Wen Sun 孙雯; Yixi Qiu 邱译曦; Yongyan Zheng 郑咏滟 (Círculo de Lingüística Aplicada a la Comunicación, 2021)
This study explores the language practices and beliefs of local employees at a Shanghai-based subsidiary of a German multinational company. We conducted a seven-month ethnographic study and collected data from the company’s publicly accessible documents, meeting transcripts, semi-structured interviews with five employees, and ethnographic notes. Qualitative data analysis revealed that local employees frequently utilized translanguaging practices despite the company’s implicit assumption that English would be used as the common corporate language. Four major translanguaging practices were identified: key terms in English, bilingual label quest, cross-language recapping, and cross-language alternation. In addition, local employees perceived language as both a resource and an obstacle, often engaging in translanguaging practices to establish their own linguistic and communicative spaces, indicating that translanguaging is a complex multilingual practice influenced by internal and external factors, subject to social milieu, personal language competence, and beliefs. Ultimately, this study extends the notion of translanguaging and probes its analytical benefits for understanding fluid and discursive activities in multilingual workplaces and the sustainability of linguistic ecology and knowledge dissemination.